Golden Syrian Hamsters as a Model for Revisiting the Role of Biological Sex Differences in SARS-CoV-2 Infection - Michita, Rafael Tomoya; Mysorekar, Indira U. (mBio, 2021)
There is growing evidence that coronavirus disease 2019 (COVID-19) affects males more severely than females, including compelling evidence indicating that biological sex is an important clinical factor influencing disease pathology and outcomes. In their recent article in mBio , Dhakal et al. find further evidence to support this hypothesis as they interrogate biological sex differences in the pathogenesis and clinical features of COVID-19 in the golden Syrian hamster model. There is growing evidence that coronavirus disease 2019 (COVID-19) affects males more severely than females, including compelling evidence indicating that biological sex is an important clinical factor influencing disease pathology and outcomes. In their recent article in mBio , S. Dhakal, C. A. Ruiz-Bedoya, R. Zhou, P. S. Creisher, et al. (mBio 12:e00974-21, 2021, https://doi.org/10.1128/mBio.00974-21 ) find further evidence to support this hypothesis as they interrogate biological sex differences in the pathogenesis and clinical features of COVID-19 in the golden Syrian hamster model. Their study probes SARS-CoV-2 infection in terms of loss of body mass, recovery, lung compromise, viral replication, inflammatory response, immune response, and, most importantly, the role of estrogen. They also demonstrate the value of a novel unbiased, quantitative chest computed tomography (CT) imaging approach. The golden Syrian hamster model holds a promising opportunity to further investigate how biological sex acts as a primary determinant in SARS-CoV-2 pathogenesis, as also demonstrated in this study.